Acoustic telemetry provides insights for improving conservation and management at a spawning aggregation site of the endangered Nassau grouper (Epinephelus striatus) - Nemeth, Richard S.; Kadison, Elizabeth; Jossart, Jonathan; Shivji, Mahmood; Wetherbee, Bradley M.; Matley, Jordan K. (Frontiers in Marine Science, 2023)
Acoustic telemetry was used to document movement patterns of the endangered Nassau grouper (Epinephelus striatus, Serranidae) over seven years at a spawning aggregation (FSA) in the US Virgin Islands. Our results showed that the Grammanik Bank, a 1.5 km2, seasonal (Feb – Apr) closed area, spatially and temporally protects Nassau grouper only 65% of time during the spawning season. Tagged Nassau grouper (n=24) arrived at the FSA after the full moon from January to May, with a peak in March, and made daily roundtrip migrations (1 - 25 km) from the FSA site. Females swam twice as far as males, while males were more sedentary and remained longer (22 d) at the FSA than females (9 d); behavioural characteristics that may cause differential bycatch mortality among sexes. The large acoustic array allowed calculation of spatially relevant areas for conservation including courtship arena (1.2 km2), staging area (4.7 km2) and primary migration pathways (9.6 km2) for Nassau grouper during spawning season, and found nearly half of all fish were temporary residents within 5 km of the FSA site for 2 to 6 months after spawning season. To improve conservation goals of this endangered species, increasing the Grammanik Bank seasonal closure to five months and its size to 6.4 km2 would increase protection to >96%. These and management recommendations incorporate the best available data to improve conservation goals by reducing potential bycatch mortality, eliminating disturbance of spawning, and protecting critical spawning habitat for Nassau grouper. These guidelines may also be applied more broadly to other Nassau grouper FSA sites located on large insular or continental shelfs areas.